2022
DOI: 10.3390/ma15030763
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Dry Chemical Synthesis of Nitrogen-Doped Activated Carbon from Bamboo Charcoal for Carbon Dioxide Adsorption

Abstract: In this work, nitrogen-doped bamboo-based activated carbon (NBAC) was in situ synthesized from simply blending bamboo charcoal (BC) with sodamide (SA, NaNH2) powders and heating with a protection of nitrogen flow at a medium temperature. The elemental analysis and X-ray photoelectron spectra of as-synthesized NBAC showed quite a high nitrogen level of the simultaneously activated and doped samples; an abundant pore structure had also been determined from the NBACs which has a narrow size distribution of microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…From the data presented in Table 1, it can be concluded that the amount of nitrogen introduced depends on the carbonization temperature; more nitrogen was introduced into activated carbons obtained at lower temperatures. Similar observations have been reported in the literature for orange peel carbons prepared with urea [24], for N-doped activated carbons from bamboo charcoal [25] and for commercial urea-modified activated carbons [26]. The decrease in nitrogen content with increasing carbonization temperature is due to the degradation of unstable thermal nitrogen groups at higher process temperatures [27].…”
Section: Resultssupporting
confidence: 86%
“…From the data presented in Table 1, it can be concluded that the amount of nitrogen introduced depends on the carbonization temperature; more nitrogen was introduced into activated carbons obtained at lower temperatures. Similar observations have been reported in the literature for orange peel carbons prepared with urea [24], for N-doped activated carbons from bamboo charcoal [25] and for commercial urea-modified activated carbons [26]. The decrease in nitrogen content with increasing carbonization temperature is due to the degradation of unstable thermal nitrogen groups at higher process temperatures [27].…”
Section: Resultssupporting
confidence: 86%
“…They determined the CO 2 adsorption capacity of NBAC under conditions of 0 • C and 25 • C at a pressure of 1 bar, which reached ranges of 3.68 to 4.95 mmol/g and 2.49 to 3.52 mmol/g, respectively. Furthermore, through ten adsorptiondesorption cycles, they confirmed the stable CO 2 adsorption performance of regenerated NBAC, demonstrating that this multifunctional NBAC exhibits excellent reproducibility and is an ideal candidate material for CO 2 capture and separation applications [138].…”
Section: Gaseous Pollutantsmentioning
confidence: 65%
“…Under this circumstance, carbon capture and storage technology were put forward to reduce the concentration of CO 2 in the air . At present, solid porous materials with high-proportion ultramicropores have exhibited outstanding performance in CO 2 adsorption fields. Zhuo used different alkali metal ions salts of carboxylic phenolic resins to prepare a series of ultramicroporous carbons by direct pyrolysis, and the CO 2 uptake could be up to 5.20 mmol g −1 at 298.15 K/1.0 bar when adding CsOH in the synthesis process . Qi used mesitylene as a raw material to synthesize the mesitylene polymer linked by the flexible methylene and carbonized the polymer with KOH at different temperatures to obtain a series of ultramicroporous carbons.…”
Section: Introductionmentioning
confidence: 99%